2015
DOI: 10.2174/1874318801509010001
|View full text |Cite
|
Sign up to set email alerts
|

Practices and Beliefs of Private Practitioners Surrounding Discounted Veterinary Services and Products

Abstract: Impacted by educational debt and stagnant salaries, the financial viability of a career in veterinary medicine is a growing concern for many within the veterinary profession. Many veterinarians are small business owners, which requires them to learn and practice good business and practice management skills. Despite the recognized importance of business skills to the success of the veterinary profession, training in this area has been historically limited. An important part of practice management skills involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…Interestingly, Kogan and colleagues found that most of the veterinarians they surveyed offered discounts on veterinary services and products on a regular basis in order to provide the best possible solution and care for their patients [36]. This finding was not confirmed by our study.…”
Section: Discussioncontrasting
confidence: 80%
“…Interestingly, Kogan and colleagues found that most of the veterinarians they surveyed offered discounts on veterinary services and products on a regular basis in order to provide the best possible solution and care for their patients [36]. This finding was not confirmed by our study.…”
Section: Discussioncontrasting
confidence: 80%
“…Relatedly, Kogan and others (2015) have emphasised that the types of pro bono work most often seen in veterinary medicine reflect an ad hoc, individual approach as opposed to an organised, systematic approach, and that this typically entails that private practitioners provide pro bono services of their own accord out of fellow feeling or a sense of duty. A management policy is supposed to save the individual veterinarian from having to be the judge of which client or animal ought to receive reduced fees or instalment agreements (Tannenbaum 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This is apparent from several studies that found low levels of adoption of some widely accepted best-practice business models among veterinarians (Brown and Silverman 1999, Cron and others 2000, Volk and others 2005, Kogan and others 2015). Veterinary ethics and business management may appear to be opposing elements of the veterinarian's professional competence, but clearly both play a direct role in situations involving financially limited clients.…”
mentioning
confidence: 99%
See 1 more Smart Citation